High electrical conductivity bipolar plate using stannum/graphite polymer composite - Farhana Masron (2018)
Nowadays, transportation is one of the promising sector for Proton Polymer Membrane Fuel Cell (PEMFC) due to the possibility of zero pollution and environment friendly vehicles and also the future expect of fossil fuels depletion . The fabrication methods of this composite and composition ratios have significant effects on its electrical and mechanical properties. This research was focused on to Graphite (G) and Stannum (Sn) as conductive fillers and Polypropylene (PP) polymer as binder. Firstly, all materials will be dry mixed using a ball mill machine with several ratios of composition. The shape of this composite was mould with the dimensions of 140 × 60 × 3 mm through the compression machine to form a bipolar plate. There were two types of composition that had been fabricated which were G/Sn and G/Sn/PP composites. Meanwhile, for G/Sn composites, two methods were applied which were sintering and compression moulding methods. For sintering method, the weight percentage of the secondary filler (Sn) is increased from 20 wt.% to 40 wt.% of the total weight percentage of fillers. Meanwhile, for G/Sn/PP, the ratio of conductive fillers and binder has been fixed at 80:20 and the ratio of conductive fillers between first and secondary filler has been varied, for G (60 to 70 wt.%) and Sn (10 to 20 wt.%). Two different types of PP polymer in powder form were used which were Low Density Polypropylene (LD-PP) and High Density Polypropylene (HD-PP). The effect of different filler material loadings on G/PP and G/Sn/PP composites properties such as electrical conductivity, bulk density, hardness and gas permeability were tested, observed and confirmed that they are able to meet the United State Department of Energy ( U.S. DOE) target properties as PEMFC bipolar plate. Results showed G/Sn produced using hot compression moulded with Sn loading of 20 wt.% of Sn loading obtained the highest electrical conductivity of 889.64 S/cm. Although the usage of the hot compression moulding method increased the value of bulk density, all results still met the U.S. DOE target which is it must be lower than 1.9 g/cm3. Other than that, hardness value for compression moulding method showed improvement compared to the sintering process method. Even though G/Sn composites for compression moulding method perform better results compared to sintered method, these composites did not exhibit good mechanical properties and showed the brittleness characteristic. These composites were also brittle. In order to overcome this weakness, PP polymer was added in G/Sn composites and the effects of PP types, Sn loading and hot compression moulding temperatures in G/Sn/PP (LD-PP and HD-PP) composites on electrical and mechanical properties were determined. Based on the results obtained, G/Sn/HD-PP composites have shown better electrical and mechanical properties as compared to G/Sn/LD-PP composites. Meanwhile, for moulding temperature for LD-PP and HD-PP were 170°C and 175°C respectively. Lastly, the optimum weight ratio of G/Sn/PP (LD-PP and HD-PP) composites was 15 wt.% of Sn loading due to high electrical conductivity, good bulk density and shore hardness value.